Sustainable Development Processes for Renewable Energy Technology - Zhironkin, Sergey; Rybar, Radim (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
To enhance the international dissemination of ideas on how to make renewable energy sources a driver of sustainable development for the coming decades, it is necessary to unite the efforts of researchers in the fields of traditional and modern energy, waste-free production, and ecology in multidisciplinary discussions of urgent problems of transition to the use of renewable energy.In order to gain new ideas and insights into these areas worldwide, this book, entitled "Sustainable Development Processes for Renewable Energy Technology", has been prepared. This book mainly covers original research integrating the principles of sustainable development, the production and recycling of new materials, and the use of renewable energy, reflecting the intended breadth of understanding of the complex interdisciplinary issues that the field of Sustainable Development Processes for Renewable Energy Technology presents.